The role of spirituality in pain, function, and coping in Individuals with chronic pain - Jensen, Mark P (2021)
Chronic pain is a multidimensional experience associated with psychosocial (e.g., pain-related beliefs and pain coping responses) and spiritual factors. Spirituality is a universal aspect of the human experience that has been hypothesized to impact pain experience via its effects on pain, physical/psychological function, resilience and pain-related beliefs, and pain coping responses. However, research evaluating the associations between measures of spirituality and measures of pain and function in individuals with chronic pain is limited. This study seeks to address this limitation.